Frogs and Toads of Northern Belize - Jenna M. Cole; Sarah K. Cooke; Venetia S. Briggs-Gonzalez; Justin R. Dalaba; Frank J. Mazzotti (EDIS)
Belize is home to several threatened frog species. One of them, the Maya mountains frog, lives nowhere else in the world. This 4-page fact sheet written by Jenna M. Cole, Sarah K. Cooke, Venetia S. Briggs-Gonzalez, Justin R. Dalaba, and Frank J. Mazzotti and published by the UF/IFAS Wildlife Ecology and Conservation Department will help you identify your frogs and toads in order to better protect them. https://edis.ifas.ufl.edu/uw439